(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
If you consider any field of human education, it is carried out in connection with a certain science, it relies on the laws of that science. This article talks about the importance of pedagogy in the formation of personality and its place in the system of sciences.